2010
DOI: 10.4081/ijas.2010.e84
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of metabolic, endrocrine and growth features in the Mexican hairless pig to determinate its potencial as model for obesity in comparison with commercial pigs

Abstract: Biochemical, endocrine and growth performance variables were evaluated and compared in the Mexican hairless (MHP) and in Landrace Yorkshires pigs (LYP) from first to ninth month of age in order to establish if the MHP could be a better model for the study of obesity than the LYP. Serum concentrations of total cholesterol (TC), triglycerides (TG), high-density lipoproteins (HDL), low-density lipoproteins (LDL), glucose, free fatty acids (FFA), and insulin were measured. Feed intake, body weight and backfat thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…Adolescent pigs fed a 5-week HFD developed an obese phenotype, having increased body weight and 46% greater back-fat depth compared with pigs consuming a LFD, which is in agreement with previous findings (25). Back fat thickness is commonly used as a measure of obesity in pigs (26,27), and increased fat deposition is associated with dysregulated gene expression (such as TCF7L2 and leptin) that are high risk susceptibility genes for type 2 diabetes and obesity (28,29). Data are presented as means with stdev.…”
Section: Discussionsupporting
confidence: 90%
“…Adolescent pigs fed a 5-week HFD developed an obese phenotype, having increased body weight and 46% greater back-fat depth compared with pigs consuming a LFD, which is in agreement with previous findings (25). Back fat thickness is commonly used as a measure of obesity in pigs (26,27), and increased fat deposition is associated with dysregulated gene expression (such as TCF7L2 and leptin) that are high risk susceptibility genes for type 2 diabetes and obesity (28,29). Data are presented as means with stdev.…”
Section: Discussionsupporting
confidence: 90%
“…Biochemical parameters in blood indicate metabolic status of pigs and they change under the influence of nutrition and breed [1]. It is very interesting that presence of metabolic adaptations in pigs fed with food that induce fat accumulation in pigs that show great fat growth [2,6,23] because they are used as a model for research in humane obesity. Newer research [16] has showed statistical importance of farm, breed and age influence on hematologic parameters in pigs.…”
Section: Introductionmentioning
confidence: 99%